2017
DOI: 10.1007/s13224-017-1052-x
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Deliveries in Cesarean Section

Abstract: Cesarean section rate has been on the rise. It is commonly perceived as a simple and safe alternative to difficult vaginal birth. However, there are situations during C section where delivery of fetus may be difficult. This can cause maternal and fetal complications. To avoid such mishaps, anticipation of potential difficulties and planning in advance can be fruitful. This amounts to mobilization of a good team of anesthetist, assistant and skilled neonatologist. Proper technical skills are needed not only to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…To prevent injuries of enormous stress to the fetus, breech delivery was most suitable. Studies have also suggested, that in cases where an inverted T-incision is not applicable, a vertical incision or a J- shaped incision are other options to consider [ 6 - 7 ]. Inverted T-incisions incidence has increased from 0.2% to 0.9%, with a remaining high risk to maternal health [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent injuries of enormous stress to the fetus, breech delivery was most suitable. Studies have also suggested, that in cases where an inverted T-incision is not applicable, a vertical incision or a J- shaped incision are other options to consider [ 6 - 7 ]. Inverted T-incisions incidence has increased from 0.2% to 0.9%, with a remaining high risk to maternal health [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 We found that pregnant women with fetal breech position (aOR = 2.39, 95% CI 1.20-4.75, P = 0.013) and transverse position (aOR = 2.89, 95% CI 1.08-7.70, P = 0.034) were more likely to have PPH than those with head position. A related study mentioned that breech position and transverse position are more likely to cause difficulty of fetal delivery during cesarean section compared with the head position, 25 which influences the contraction of the uterus and is probably the main reason for increasing the risk of PPH. In this study, we found no correlation between the type of scarred uterus and PPH (P = 0.74), indicating that our prediction model is suitable for all pregnant women with a scarred uterus, whether the scarred uterus is caused by hysteromyomectomy or cesarean section.…”
Section: Figurementioning
confidence: 99%
“…In addition to the cesarean section and myomectomy, the history of other intrauterine surgery, such as endometrial curettage, is a risk factor for PPH in some reports. 25 Intrauterine surgery may damage the endometrium and affect the placenta attachment and growth, which can lead to placenta previa or PAS 26,27 and contribute to the occurrence of PPH finally. In this study, it showed that the history of other intrauterine surgery was not significantly related to PPH (P = 0.437).…”
Section: Figurementioning
confidence: 99%
“…It is a life-saving operation undertaken in situations when normal vaginal delivery of a baby has become difficult. It is an obstetrically practiced procedure which has become very commonly in use, and which is rising in popularity among women all over the world (Dalvi 2018; Chopra 2016). The increase, according to Byamugisha and Adroma (2020, p.1) is attributed to diverse issues relating to: "patient, institutional, care provider and societal factors."…”
Section: Introductionmentioning
confidence: 99%